Operation strategies of battery energy storage systems for preventive and curative congestion management in transmission grids. Issue 3 (29th December 2022) - Lindner, Martin; Peper, Jan; Offermann, Nils; Biele, Charlotte; Teodosic, Milijana; Pohl, Oliver; Menne, Julian; Häger, Ulf
Abstract: Anticipating and relieving congestions is an ongoing challenge for transmission system operators. Distributed grid‐scale battery energy storage systems enable operators to shift power flows and remedy congestion through virtual power lines and grid boosters. This paper includes battery energy storage systems in a combined preventive and curative congestion management optimization. First, it analyzes the impact of the two operational strategies in a case study of the German transmission grid. Furthermore, it outlines curative ad‐hoc measures to overcome uncertainties during operational planning and real‐time operation. The simulation results indicate that battery energy storage systems further increase the use of curative measures and reduce congestion management costs. Abstract : This paper demonstrates how grid‐scale battery energy storage systems can be integrated into preventive and curative congestion management optimization. A case study investigates the impact of virtual power lines and grid boosters on congestion management results for the German transmission grid.